2010
DOI: 10.1021/jp101392g
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a White-Light-Emitting Diode by Doping Gallium into ZnO Nanowire on a p-GaN Substrate

Abstract: This study evaluated a process for fabricating white light emitting diodes (LEDs) by doping Ga into ZnO nanowires (ZnO:Ga NWs) on p-GaN substrates. Vertically aligned ZnO:Ga NWs were grown by thermal chemical vapor deposition to 0.7 μm in length and 50−300 nm in diameter. The white light LED was successfully fabricated by forming an n-p-n heterojunction on an ITO/glass substrate. The electroluminescence (EL) emission peak was 500 nm, and the broad band fwhm intensity was 200 nm. Finally, photographs show a whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 24 publications
0
59
0
1
Order By: Relevance
“…Second, a large number of excited electrons are stored at the tips of NWs, thereby causing a subsequent point discharge that reduces the electric field. [41][42][43][44][45][46][47] This article provides a helpful review on doping ZnO 1D and 2D nanostructures. First, the synthesis methods for and the properties of doped ZnO 1D and 2D nanostructures are introduced and discussed.…”
Section: B3014mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a large number of excited electrons are stored at the tips of NWs, thereby causing a subsequent point discharge that reduces the electric field. [41][42][43][44][45][46][47] This article provides a helpful review on doping ZnO 1D and 2D nanostructures. First, the synthesis methods for and the properties of doped ZnO 1D and 2D nanostructures are introduced and discussed.…”
Section: B3014mentioning
confidence: 99%
“…FE cathodes from ZnO nanostructures have gained significant interest because of their valuable properties, including their high aspect ratio, low work function, general stability, and high electrical conductivity. [41][42][43][44][45][46][47] Compared with other materials, such as GaN, ZnO exhibits better characteristic and potential to fabricate UV photosensors. Highperformance solid-state UV photosensors have attracted interest in recent years.…”
mentioning
confidence: 99%
“…ZnO 纳米线/棒阵列具有长径比高 [6] 、比表面积大 [7] 及电子注入效率高 [8] 等优点, 在发光二极管 [9] 、 纳米发电 机 [10] 、染料敏化太阳能电池 [11] 、紫外探测器 [12] 和气体传 感器 [13] 等领域具有重要应用. 高质量的 ZnO 纳米线/棒 阵列是提高器件性能的决定因素 [10,14] .…”
Section: 引言unclassified
“…[13][14][15][16][17][18][19][20] Zhu et al [13] deposited undoped nZnO thin films on p-GaN substrates using molecular beam epitaxy (MBE) to form an n-ZnO/p-GaN heterojunction. Under back-illumination conditions, the photodetector shows a UV photoresponse in a narrow spectrum window within 360-390 nm and a low peak responsivity of 1 × 10 −6 A/W at zero bias.…”
Section: Introductionmentioning
confidence: 99%
“…With high sensitivity to UV light, the high density of surface trap states, and a much higher surface area-tovolume ratio, one-dimensional ZnO nanostructures such as nanorods (NRs) or nanowires can improve the properties of photodetectors. [15][16][17][18][19][20] Chen et al reported a UV photodetector based on a ZnO nanowire/p-GaN heterojunction. [17] The heterojunction device in the dark showed a low reverse leakage current and large illuminated current.…”
Section: Introductionmentioning
confidence: 99%